Emerging Challenges of Women Entrepreneurs in Nepal - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2022)
Women's entrepreneurship is a new concept in Nepal. The women had engaged in micro-cottage and small skill enterprises to contribute to their career development. They have been overcoming many problems to make the job successful. The study's objective was to identify multiple difficulties that women entrepreneurs face before and after starting their enterprise and to examine the knowledge of various aspects of business that Nepalese women entrepreneurs have before starting their businesses. This study adopted a descriptive research design. Primary data was the main source and was collected through survey questionnaires of women entrepreneurs. The total sample was 200 women entrepreneurs selected through purposive sampling throughout Kathmandu valley. Data has been processed in the computer using SPSS. Descriptive statistics such as mean and standard deviation were applied to analyze data. The study found that the four major problems faced by women entrepreneurs were acquiring working capital, managing new ventures, getting a labor force, and marketing the products.